PENGARUH LAJU ALIR UDARA, FAKTOR UDARA DAN SUHU TERHADAP KOMPOSISI GAS - Djeni Hendra (Jurnal Penelitian Hasil Hutan, 1992)
The  result of gasification study using Albazia falcataria and  Eucalyptus deglupte wood is reported  in this paper,  using fluidized bed system   with an  air flow rate  varied  between   2,8  -  4.0  m3/hr.  air factor   between  0.22  -  0.34   and  bed  temperature    ranging  from 742 - 895ᵒC.The aim of the  study  is to  obtain   the best  treatment   is the  proses of fluidized bed.  The  result  shows that the gascous product (%.  Volume ) for  Albazia falcateria Varies from 51.81 -  61.94 %  (N2),  0.16-0,75  %  (O2), 13.52- 19.13  %  (CO2),  10.05 -  13.00  % (CO) , 4.19  - 6.41  %  (H2) ,  2. 2 7 -  5. 87  %  (CH4).   The figures  for   Eucalyptus deglupta were  54. 55  -  58; 06  %  (N2)  , 0.14  - 0. 18  % O2), 16.09-   18.81   % (COz), 11. 22 - 13.06  % (CO) , 7. 72 - 9. 73 (H2),  3.83 - 4.93  %  (CH4).in addition   C2H4 and C2H6 gas  were produced  in small  quantity from   each  species.